Some epidemiological aspects of Karnal bunt of wheat - K.D. SRIVASTAVA and R. AGGARWAL, VIVEK S. SIDHARTHA, D.V. SINGH (Indian Phytopathology, 2002)
Epidemiological studies taken up on Karnal bunt (Neovossia indica ) of wheat revealed that the density and the viability of teliospores were reduced with the increase of soil depth. Effect of snowing and thawing also showed that chilling reduced viability of teliospores and prolonged the germination period. Therefore, the chances of disease occurrence where snowing occurs, are very rare. The diurnal periodicity in release of secondary sporidia was observed which showed that maximum sporidia were released between morning hours 2.0-6.0 AM under high relative humidity and leaf-wetness. The sporidial release was negatively correiated with solar radiation and wind speed. The sporidial count was more at lower heights during last week of February to 1st week of March, which coincides with the anthesis period of the crop. Low temperature (15Â°C) before inoculation predisposed the host to infection, whereas an optimum post-inoculation temperature (l8Â°C) was favourable for spread of disease in the spike